Exploiting globalization potential: U.S. and japanese strategies - Johansson, Johny K.; Yip, George S. (Strategic Management Journal, 1994)
Abstract This paper develops a model of global strategy that includes the constructs of industry globalization potential, the use of global strategy, the role of organization and management and the performance consequences of using global strategy. Propositions are developed as to why American and Japanese MNCs might differ in their perceptions of industry globalization potential, in their desired global strategy response, in their organizationally‐derived ability to implement global strategy and in their resulting performance. The model and arguments are examined in extensive interviews with senior executives at 36 worldwide businesses belonging to some of the largest American and Japanese MNCs. Data are analyzed using a partial least squares causal model. The results show that the Japanese firms have more globalized stategies than do the Americans, and that this factor affects their performance favorably.